GLP-1 based therapeutics: simultaneously combating T2DM and obesity - Heppner, Kristy M.; Perez-Tilve, Diego (Frontiers in Neuroscience, 2015)
Glucagon-like peptide-1 (GLP-1) enhances meal-related insulin secretion, which lowers blood glucose excursions. In addition to its incretin action, GLP-1 acts on the GLP-1 receptor (GLP-1R) in the brain to suppress feeding. These combined actions of GLP-1R signaling cause improvements in glycemic control as well as weight loss in type II diabetes (T2DM) patients treated with GLP-1R agonists. This is a superior advantage of GLP-1R pharmaceuticals as many other drugs used to treat T2DM are weight neutral or actual cause weight gain. This review summarizes GLP-1R action on energy and glucose metabolism, the effectiveness of current GLP-1R agonists on weight loss in T2DM patients, as well as GLP-1R combination therapies.